Report on the 2018 Magnetic Prospection at Artaxata/Artashat in Armenia - Lichtenberger, Achim; Meyer, Cornelius; Zardaryan, Mkrtich H. (Archäologischer Anzeiger, 2020)
In 2018, a new Armenian-German archaeological project started in the city of Artaxata/Artashat close to Khor Virap, Armenia. The project aims at the investigation of the settlement history of the capital of the Artaxiad Kingdom. Previous archaeological work has focused on the main hills of the city and has underlined the wealth of the material culture of the city and its entanglement with the Mediterranean, Iran and the Northern Caucasus. The new project focuses on the lower city of Artaxata and the paper reports the geophysical work of the first campaign. In total, an area of approx. 11.2 hectares was covered by magnetic prospections and the results suggest that several monumental architectural structures once stood in the lower city and that these structures belonged to the same planning as the Artaxiad constructions from the upper city. Furthermore, the prospections provide indications about the infrastructure of the city and form the basis for the work in the upcoming years.